An analytical solution for evaluating the effect of steel bars in cracked concrete. (September 2016) - Mi, Zhengxiang; Li, Qingbin; Hu, Yu; Xu, Qianjun; Shi, Jie
Highlights: An analytical solution was proposed for assessing the effect of steel bars on crack. The bridging traction was deduced from the deformation of steels. The ultimate load-carrying capacity was accurately predicted. A complete fracture process of reinforcement concrete structure was reproduced. The influence of different parameters on mechanical response was investigated. Abstract: An analytical solution is proposed for investigating the mechanical behavior of a crack in steel-reinforced concrete. In this solution, an elastic–plastic constitutive law was assumed to satisfactorily describe the behavior of the steel bar, and the bridging traction was deduced from the deformation of steels. The curves of the load versus crack mouth opening displacement predicted by the proposed method could be fitted to experimental results. It was analytically demonstrated that the ultimate load-carrying capacity calculated by the developed method is not sensitive to the shape of the softening curve for a large beam with high reinforcement ratio.